(untitled) (Fiep Bulletin - online, 2014)
The relays are often used in swimming training as a funny way of produce dispute between the athletes. Thus, the sport becomes funny for them and athletes do their training with more pleasure and determination, especially if the athletes are children. Usually coaches organize the relays choosing some "team captains". Then, the team captains choose the other athletes of their respective team. This method often generates some relays teams much stronger than others, thereby reducing the effectiveness of the training. This paper presents a methodology that, by using specific software, automates the selection of relay’s team members and assembly relays with similar performance. Thus, increase the competitiveness between the teams and helps the training to achieve their goals. Finally, the practical results of the use this methodology at a real training of a swimming team are presented and discussed.